A case of bi-ventricular extensive calcification caused by multiple factors - Xiaoyan Tu; Zhihui Hu; Kevin Yang; Zhuoqing Hu; Yi Jiang (BMC, 2020)
Abstract Background Extensive myocardial calcification has a low incidence rate, but when the patients do have extensive myocardial cases, the prognosis is usually poor. Several sepsis-related extensive myocardial calcification cases have been reported, but there are cases of biventricular calcifications that are caused by multiple cases besides bacteremia and the treatment for it has a low percentage of success. Case presentation A 9 year old girl had an extensive biventricular calcification which is caused by multiple factors including multiple organ failure (heart, lung, liver, and kidney), aseptic cardiomyopathy, systemic inflammatory response syndrome, pulmonary hemorrhage, viral encephalitis. In this case study, the massive myocardial calcification present in the patient was classified as dystrophic. After the patient was transferred to the Intensive care unit, a series of rescue treatments such as anti-inflammatory factor storm were implemented to protect the organs. In the end, the patient was rescued from the rescue treatment procedure. After 18 months of follow-up, it was observed that the patient's heart function returned to normal and it was observed that there was no change in myocardial calcification in the patient. Conclusion In this case study, it showcased a case of the diffused biventricular calcification that caused by multiple factors. Furthermore, the precise role of calcification on cardiac function was largely unknown and there has to be further follow-up observation on the patient.